MODERN INTRAOCULAR LENS DESIGNS - Buckhurst, Phillip (International Journal of Allied Health Sciences, 2021)
Since the implantation of the first intraocular lens (IOL) in 1949, there have been significant improvements in their design transforming cataract surgery into a precise refractive surgical technique. In recent years accommodating, multifocal, EDoF and toric IOLs have been developed to reduce spectacle dependence following cataract surgery. With the growing popularity of these IOLs, optometrists need to be familiar with the optical of each lens design in order to address the challenges posed when assessing patients implanted with such IOLs. This presentation will provide an overview of what an optometrist needs to know when assessing a patient implanted with these advanced IOL designs.